2007
DOI: 10.1002/bdrb.20116
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aconitine toxicity in rat embryos in vitro

Abstract: Our study showed that Aconitine had direct embryotoxic effects during the rat organogenetic period. NOAEL was about 1 microg/ml and metabolism in S9 mix could induce the attenuation of Aconitine toxicity. Until more is known about the effects of Aconitine in pregnant women, we suggest its use should be treated with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…No publications were found to show that this interesting bioactivity has been properly studied as yet. Until more is known, practitioners should be rigorously cautious in administering to pregnant women, since a recent study showed that AC had direct embryo-toxic effects in rats during the organogenetic period (Xiao et al, 2007).…”
Section: Therapy Of Abdominal Colic and Irregular Menstruationmentioning
confidence: 99%
“…No publications were found to show that this interesting bioactivity has been properly studied as yet. Until more is known, practitioners should be rigorously cautious in administering to pregnant women, since a recent study showed that AC had direct embryo-toxic effects in rats during the organogenetic period (Xiao et al, 2007).…”
Section: Therapy Of Abdominal Colic and Irregular Menstruationmentioning
confidence: 99%
“…As far as we know, the toxicity of exposure is mainly related to neurological, cardiovascular and gastrointestinal systems, [24][25][26] and sometimes embryotoxicity. 27 The damage to hepatocytes and nephrocytes caused by aconitum alkaloids cannot, however, be ignored, particularly when it is combined with other herbs and/or chemical drugs. Transporters as a superfamily of proteins, which act as barriers to xenobiotics crossing the cell membrane, are critical for the fate of chemicals in vivo, including the pharmacokinetic pattern, safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…As methods of evaluating drug safety continue to improve, they have included experiments during the teratogenic sensitivity period, in vitro whole embryo culture and other methods, all of which can be used to evaluate the safety of CM (Han et al, 2014). Xiao et al used whole embryo culture to explore the effects of aconitine on rat embryos during their critical period of organogenesis and found that a concentration of 5 μg ml −1 of aconitine could induce severe dysmorphogenesis, including cardiac defects (undivided cardiac tube and inflated pericardial cavity), irregular somites and brain malformation (e.g., narrow brain vesicles) (Xiao et al, 2007). Whole embryo culture in rats revealed that the essential oil of Curcuma zedoaria produced a concentration-dependent toxicity ex vivo in the embryos, and led to weight loss as well as abnormal haematological and biochemical effects on pregnant females and their embryos (Zhou et al, 2013).…”
Section: Chinese Medicines For Pregnancymentioning
confidence: 99%